Alchornea cordifolia leaf-extract ameliorates bisphenol A-induced obesity in male Wistar rats - Abdulhakeem Rotimi Agboola; Ako Hogan Itam; Chinedum Martins Ekeleme; Eyuwa Ignatius Agwupuye; Zuwairatu Oyiza Ahmed; Godswill Peter Igiakong; Gideon Bassey Agbor; Asmau Niwoye Abubakar; Zainab Adamu; Esien David-Oku; Item Justin Atangwho (Clinical Phytoscience)
Abstract Background Bisphenol-A (BPA), a chemical impregnated into plastic bottles which has been linked to obesity and its associated health problems, was used to induce obesity in this study. The cost and reported limitations and side effects of orthodox medications employed for weight management, have necessitated a shift in attention to medicinal plants, given their comparative advantage and the common belief amongst locals that plants are free from negative side effects. One plant that has found application for weight loss amongst the local population in Nigeria is Alchornea cordifolia which commonly grows in Africa and has been confirmed to possess numerous medicinal properties including anti-inflammatory, anti-diarrheal, hepaprotective, antiviral, and anti-diabetic effects. Objective To evaluate the obesity attenuation effect of Alchornea cordifolia ethanol extract (ACEE) and other associated macrovascular health risks in BPA-induced obesity rat model. Methods Thirty (30) young male Wistar rats (80–100 g) divided into five groups of six rats each, were administered BPA (50 mg/kg), once a day, p.o. for four weeks in order to induce obesity. Afterwards, obesity was confirmed using anthropometric indicators, and the animals were treated for another four weeks as follows: Group 1 (Normal control) received drug/extract reconstitution solvent, olive oil, Group 2 (obese control) received 50 mg/kg of BPA, Group 3 received a conventional anti-obesity drug, Orlistat (30 mg/kg), Group 4 received ACEE (500 mg/kg), and Group 5 received ACEE (1000 mg/kg). At the end of study, anthropometric indicators and relevant serum biochemical indicators were determined using standard procedures. Results The results obtained showed that oral BPA administration caused obesity i.e. increased body weight, Lee’s Index and waist circumference, compared to the normal control (p < 0.05). Moreover, BPA treatment was found to alter measured serum biochemical indicators, (FBG, lipid profile, liver and kidney function indicators) and the lipid regulating enzymes (pancreatic lipase and HMG-CoA reductase activities), relative to the normal control (p < 0.05). However, upon 4-week ACEE oral treatment at 500 and 1000 mg/kg b.w., there was observed significant attenuation of the anthropometric indices, serum biochemical indices and lipid metabolizing enzymes studied (p < 0.05). Conclusion Together, the results obtained from this study have scientifically validated the traditional use of Alchornea cordifolia leaves in body weight control, hence suggest that the leaves may possess natural products useful in the management of obesity and its related complications.